Book Review: América Latina en la transición demográfica (1800-2050) [Latin America in the Demographic Transition (1800-2050)], by Héctor Pérez Brignoli - Zavala de Cosío, María Eugenia (2023)
This is a commentary on the book América Latina en la transición demográfica (1800-2050) [Latin America in the Demographic Transition (1800-2050)], by Héctor Pérez Brignoli, published by Teseo Publishing House, Buenos Aires, Argentina, in collaboration with the Centro Centroamericano de Población (CCP) [Central American Center for Populations], of the University of Costa Rica (UCR). Through seven chapters and an epilogue, this book contributes to knowledge of Latin America's demographic transition. This is a work based on detailed studies of different countries and documented with many international comparisons; in addition, it is supported by current advances in the field of demography and population studies. Its reading is recommended for students and specialists in demography but also for the general public interested in these topics.